Mainstreaming of Out-of-School Children with Community Support A Study - Tripathy, Kamala Kanta (JOURNAL OF INDIAN EDUCATION, 2015)
One of the stumbling blocks on the road to achieve education for all is out of school children in the age group 6 to 14. To address the issue out of children, the All India Primary Teachers’ Federation conducted a study in 2014-15 to bring out of school children in the age-group 6-14 to the mainstream with the support the community. The study was conducted in the states of Tamilnadu and Odisha. Investigators were selected to conduct household survey in the selected villages to identify out of school children. In Odisha, the investigators identified 544 (283 boys and 261 girls) out of school children in the age-group 6-14. Out of these 544 children, 325 (175 boys and 150 girls) in the age group 6-14 were mainstreamed into schools in their neighbourhood with the support of community leaders. In Tamilnadu 46 (25 boys and 21 girls) are out of school children in the age group 6-14 were identified by the investigators. Of these, 43 (23 boys and 20 girls) were mainstreamed into class appropriate to their age in neighbourhood schools. But for this project, out-of-school children both in Tamilnadu and Odisha states might have remained illiterate throughout their lives.